Motivação e presença social em chats para formação de professores multiplicadores de inglês instrumental - Matarazzo, Roberta Gomes (2007)
Online education is present in the society we live as a dynamic and attractive way of learning. The online environment uses computer mediated communication (CMC) through synchronous or asynchronous tools, as for instance, chats, e-mails, etc, as a means to promote interaction among courses participants. Being the chat a proper place to the different types of interactions occur, that highlights a social side, the aim of this work was to observe which motivational factors and/or social indicators were present in the interactions that took place in the interactions of the five chat sessions that took place in the online part of semipresencial course called instrumental reading, offered to the education of teachers. The theoretical reference that supports the present study relies upon Dörney s (1998) concept of motivation presented, and the motivational categories and constructs presented by Miltiadou e Savenye (2003). Since motivational factors are important to students maintenance in the course. Moreover, in order to have a welcoming environment, it is necessary the occurrence of Social Presence according to Garrison and Anderson s (2003) model of the community of inquiry. The data were explored quantitatively (frequency of turns) and qualitatively (motivational categories and Social Presence categories and indicators). The results suggest that the interaction which occurred among the participants was favorable to reach the goals of the chats, in addition to this, we concluded that if the social indicators are not present, the subject does not show the motivational constructs. That relationship seems to happen due to the fact that motivation is social oriented